Financial Capital Inflows, poverty Alleviation and the role of institutional qualities: The Nigerian Experience in a case of multiplicative interaction Modeling - Asemota, Georgina; Igweagbara, Gladday (Acta Universitatis Danubius. Œconomica, 2023)
The growth-enhancing potency of Foreign Capital Inflows has raised policy concerns for sustainable development agenda in emerging countries. This study examined the intermediating effects of institutions on the impact of Financial Capital Inflows on Poverty alleviation in Nigeria. The study deviated from the norm of using health, education, or HDI as proxies for poverty by using Food Security instead. The institutional mediating variables employed were Voice and accountability, Political Stability, Corruption, Rule of Law, and Governance efficiency. The principal component of government monetary, fiscal, and trade policies was used as the control variable. Six multiplicative interaction models were constructed. Data from 1996 to 2021 were sourced and the Restricted Error Correction Autoregressive Distributed Lag (RECM-ARDL) technique was employed as the estimation technique. The results confirm that institutions significantly interact with the impact on financial capital inflows and poverty alleviation. Corruption and Political Stability were the most significant mediating variables in determining the potency of financial capital inflows in alleviating poverty in Nigeria. The result empirically supports the need to strengthen institutions in Nigeria as a veritable means of improving the ability of financial capital inflows to enhance sustainable development in Nigeria.